Practical data migration - Morris, John (British Computer Society, 2006)
Annotation
Print version record
Keywords: Database management; Electronic data processing; Bases de données; Gestion; Databases; Database programming; COMPUTERS / Data Modeling & Design; COMPUTERS / Data Processing; BUSINESS & ECONOMICS / Mergers & Acquisitions; Database design & theory; Information architecture; Data capture & analysis; Takeovers, mergers & buy-outs